ANALISIS FAKTOR YANG MEMPENGARUHI IPK MAHASISWA TERHADAP PENENTUAN KUALITAS PROSES PEMBELAJARAN DENGAN METODE ELECTRE II - Riski Yanti; Agus Perdana Windarto; Suhada Suhada (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
This study aims at what factors influence the value of Student GPA in StikomTunas Bangsa Pematangsiantar. Data used is obtained by giving questionnaires to students of STIKOM Tunas Bangsa Pematangsiantar. With alternatives used, namely curriculim, intelligence, absenteeism, and value. While the criteria used are the names of respondents who answer a question. The method used in this study is Electre II. From the results of the ELECTRE II calculation, the third alternative A3 is obtained as the first rank, A2 as the second rank, A4 as the third rank, and A1 as the last alternative. It is hoped that this research can be used by the education as teaching material for the students' academic success and progress.Keywords: Students, GPA,  Decision Support System, ELECTRE II